Infecção latente por mycobacterium tuberculosis - (:unkn) unknown (Universidade Federal do Amazonas, 2013)
Exposure to Mycobacterium tuberculosis can trigger three distinct events in the human body, which are: elimination of bacilli; latent infection, where there is infection control, but not its elimination; or development of tuberculosis, when the immune response is insufficient to contain the infection. Undergraduate nursing students can become exposed to these bacteria, due to their curricula activities. The purpose of this study was to identify latent tuberculosis infection and its associated risk factors among undergraduate nursing students according to their college year. This is an epidemiological, cross-sectional, case detection study with primary collection of data on knowledge and situation of latent tuberculosis infection among first and last year undergraduate nursing students from the Federal University of Amazonas and the University of the State of Amazonas in which were conducted test release interferon-gamma (Quantiferon TB Gold in Test) and Tuberculin Test to detect TB infection . Data were analyzed using the Statistical Package program for the Social Sciences in univariate approaches for describing the distribution of variables, and bivariate approaches to identify how variables relate to each other and the associated risk factors within latent tuberculosis infection . The first year students test results showed positive in four cases simultaneously, while the last year students results detected both positive results in a single individual. The total of 38 positive test results was obtained in correspondence to 33 students at both universities. Statistically significant differences were detected between the first and last year students, and the age group with positive result for Tuberculin Test as well as latent infection, use of Tuberculin Test to guide treatment, sharing environments with patients and mandatory reporting of case tuberculosis situation with first or last year students. Data from this study allowed a profile analysis of the students and compared it between the groups of first and last years. We suggest Nursing Schools better preparation for learning more accurately about tuberculosis.
Keywords: Tuberculose latente; Estudantes de Enfermagem - Mycobacterium tuberculosis; Mycobacterium tuberculosis; Infecção latente por tuberculose - Estudantes de Enfermagem; CIÊNCIAS DA SAÚDE: SAÚDE COLETIVA